Assessment Of Water Resources In Wadi Siham Basin, Yemen - Al-Ward, Majed Ahmed Abdullah (2013)
Wadi Siham Basin is one of the most important agricultural areas in the country. This study aims to assess the surface water resources in Wadi Siham Basin in terms of source, quantity and spatial and temporal variation. The main focus of the study was to investigate the groundwater balance beside evaluating the rainfall and runoff trend annually and seasonally and also evaluating the quality and quantity of groundwater resources. The relationship between availability and the uses of groundwater and water balance was also evaluated. The results indicated that the total average of annual rainfall was 346.39 mm/year from 1979 to 2008, while the total volume of rainfall was 1711.26×106 m3. The mean annual surface water runoff from 1990 to 2009 was 82.92×106 m3 equivalent to 4.85% of the total volume of rainfall precipitated on Wadi Siham Basin. The largest amount of water loss was by evapotranspiration amounting to 1480.81×106 m3 (86.53%) while only 147.53×106 m3 (8.62%) lost to the ground. A total of 570 events of flood occurred from 1990 to 2009 with a mean annual flood of 53.10×106m3. The rainfall and runoff trends based on Mann-Kendall test and Sen’s slope analyses results showed that the significantly negative (P<0.05) at two stations; Wallan (Sen’s slope = -4.72 mm/year) and Al- Amir stations (Sen’s slope = -6.11 mm/year). A positive trend, however, occurred in one station (AREA station, Sen’s slope = 50.20 mm/year). A total annual groundwater recharge (input) of the coastal aquifer system was 147.53×106 m3/year and the discharge (output) was 202.57×106 m3/year indicating that the aquifer system was overexploited.